2003
DOI: 10.1159/000069353
|View full text |Cite
|
Sign up to set email alerts
|

Topographical Organization of an Indirect Telencephalo-Cerebellar Pathway through the Nucleus paracommissuralis in a Teleost, <i>Oreochromis niloticus</i>

Abstract: The nucleus paracommissuralis (NPC) of teleosts is a relay nucleus of an indirect telencephalo-cerebellar pathway. However, cells of origin in telencephalic subdivisions and terminal patterns of the NPC fibers in the cerebellum remain unclear. We studied these issues by means of tract-tracing methods in a cichlid, tilapia (Oreochromis niloticus). After tracer injections into the NPC, retrogradely labeled cells were found bilaterally in dorsal and ventral regions of the area dorsalis telencephali pars centralis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
69
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 33 publications
10
69
1
Order By: Relevance
“…The holocentrid CC receives additional afferents from the torus longitudinalis and nucleus subvalvularis present study], which were not found in previous CC injection studies of other teleosts. Our results show that the CC receives massive projections from the NPC and NLV as has been reported previously in other teleosts [Wullimann and Northcutt, 1988;Imura et al, 2003]. However, projection patterns of the NPC and NLV to the CCd and CCv are rather different.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The holocentrid CC receives additional afferents from the torus longitudinalis and nucleus subvalvularis present study], which were not found in previous CC injection studies of other teleosts. Our results show that the CC receives massive projections from the NPC and NLV as has been reported previously in other teleosts [Wullimann and Northcutt, 1988;Imura et al, 2003]. However, projection patterns of the NPC and NLV to the CCd and CCv are rather different.…”
Section: Discussionsupporting
confidence: 88%
“…The NPC is known as a relay nucleus of an indirect telencephalo-cerebellar pathway in acanthopterygian teleosts [Ito et al, 1982;Imura et al, 2003;Xue et al, 2003]. The nucleus receives descending visual projections from the telencephalon and project to the CC [Ito et al, 1982;Xue et al, 2003].…”
Section: Afferents From the Diencephalonmentioning
confidence: 99%
“…For the most part, our Dc groups are similar to Dc groups recognized previously and, in some cases, it is possible to hypothesize about their relationship to other groups of D. For example, our Dc-3 is similar to goldfish Dc and appears to be closely associated with Dm-3. Caudally, we recognized two Dc groups (Dc-4 and Dc-5) that appear closely associated with Dl and are similar to cell groups in tilapia that are part of the indirect telencephalo-cerebellar pathway [Imura et al, 2003]. In other cases, the relationships are less clear.…”
Section: Discussionmentioning
confidence: 80%
“…In vertebrates, the cerebellum is one of the most variable brain parts in terms of shape and size [Butler and Hodos, 1996]. However, despite the notable macroanatomical variability, the cerebellum of teleost species plays an important role in monitoring incoming sensory information and in providing online adaptation of not only motor but also nonmotor functions to perform contextually relevant behaviors, even spatial cognition [Imura et al, 2003;Salas et al, 2008]. Thus, we hypothesize that a welldeveloped cerebellum allows fish larvae to improve their chance of successful recruitment after a long pelagic phase in the ocean.…”
Section: Relationship Between Brain Organization and Life History Tramentioning
confidence: 99%